Acute targeting of N-terminal tau protein has long-lasting beneficial effects in Tg2576 APP/Aβ mouse model by reducing cognitive impairment, cerebral Aβ-amyloidosis, synaptic remodeling and microgliosis later in life - Valentina Latina; Margherita De Introna; Francesca Malerba; Rita Florio; Bijorn Omar Balzamino; Giuseppe Di Natale; Michele Francesco Maria Sciacca; Giuseppe Pappalardo; Alessandra Micera; Annabella Pignataro; Pietro Calissano; Giuseppina Amadoro (Acta Neuropathologica Communications)
Abstract Even though the number of patients suffering from Alzheimer’s Disease (AD) is rapidly growing worldwide, only a few symptomatic treatments have been approved for clinical use, pointing out the urgent need for more effective disease-modifying therapies that actually alter the progression of this neurodegenerative disorder which is characterized by co-occurence of both Amyloid beta (Aβ) and tau neuropathologies. Preclinical and clinical evidence suggests that a link between Aβ and tau drives the entire continuum of AD pathobiology. 12A12 is a monoclonal antibody (mAb) which offers neuroprotection into two transgenic lines of AD, including Tg2576 that overexpresses Swedish mutation (KM670/671NL) of Amyloid Precursor Protein (APP, isoform 695) and 3xTg (APP Swedish, MAPT P301L, and PSEN1 M146V), by targeting the 20-22kDa N-terminal tau fragments (NH2htau). In particular, acute (over 14 days with 4 doses), intravenous injection of 12A12mAb leads to significant improvement of cognitive, biochemical and histopathological AD signs in symptomatic 6-month-old Tg2576, a well-established transgenic mouse model that mimics the human amyloidosis with an age-dependent Aβ accumulation/aggregation and plaque deposition. Here, we report that Tg2576 mice, immunized with 12A12mAb at 6 months of age and returned to their home cage for additional 3 months, exhibit preserved spatial memory despite the anticipated interruption of antibody administration (discontinuous treatment). This enduring beneficial effect on memory deficit (up to 90 days after the last injection) is accompanied by normalization in the synaptic imbalance and microgliosis along with decrease of the most toxic A11-positive prefibrillar oligomers and inverse increase in 4kDa monomeric form(s) of Aβ 1–42. These findings reveal that: (i) soluble, pathogenetic tau specie(s) located at the N-terminal domain of protein early synergizes with Aβ in driving the progression of AD neuropathology; (ii) transient immunoneutralization of the NH2htau following short-term treatment with 12A12mAb exerts preventive, long-lasting neuroprotective effects, at least in part by interfering at “pre-plaque” stage with the progressive deposition of insoluble, fibrillar Aβ via a shift of its aggregation pathway into its less harmful, unaggregated monomeric forms. Taken together, these findings represent a strong rationale for the advancement of 12A12mAb to clinical stage aiming at preventing the Aβ-dependent neurodegeneration by lowering the cerebral levels of NH2htau in humans suffering from chronic, slow-progressing AD.